The Real Contribution of The Pinjam Pustaka Literacy Community in Developing Children's Interest in Reading in Sorong City - Nasrulloh, Lalu; Fatimah, Ariyani; Yusviranty, Rara Dwi (Interference: Journal of Language, Literature, and Linguistics, 2024)
Abstract. This research aims to find out the real contribution of the Pinjam Pustaka literacy community in developing children's interest in reading in Sorong City. This research is descriptive qualitative type. This method is used because it can emphasize the search for meaning, the description of phenomena, and is presented in narrative form. The source of data in this research is in the form of statements submitted by the founder and volunteers of Pinjam Pustaka about the role or contribution of Pinjam Pustaka in developing children's interest in reading. The results obtained in this study are that Pinjam Pustaka takes various concrete steps in developing children's interest in reading in Sorong, such as providing quality and diverse reading materials. Pinjam Pustaka also does not close itself in terms of its literacy movement, but rather opens space for collaboration with various parties. On the other hand, in its literacy efforts, Pinjam Pustaka also experiences obstacles such as the availability of resources, because it is considered quite overwhelmed in serving the increasing number of visitors. Keywords: Literacy Community, Borrow Library, Reading Interest, Sorong.